2021
DOI: 10.3389/fimmu.2021.685978
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages, as a Promising Strategy to Targeted Treatment for Colorectal Cancer Metastasis in Tumor Immune Microenvironment

Abstract: The tumor immune microenvironment plays a vital role in the metastasis of colorectal cancer. As one of the most important immune cells, macrophages act as phagocytes, patrol the surroundings of tissues, and remove invading pathogens and cell debris to maintain tissue homeostasis. Significantly, macrophages have a characteristic of high plasticity and can be classified into different subtypes according to the different functions, which can undergo reciprocal phenotypic switching induced by different types of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 182 publications
0
19
0
Order By: Relevance
“…It has also been reported that CALD1, a key gene associated with cancer-associated fibroblasts, can promote the progression of bladder cancer by remodeling the tumor microenvironment [ 24 ]. By modifying the tumor immune milieu, macrophages regulate malignant capabilities of colorectal cancer, according to Zhang et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that CALD1, a key gene associated with cancer-associated fibroblasts, can promote the progression of bladder cancer by remodeling the tumor microenvironment [ 24 ]. By modifying the tumor immune milieu, macrophages regulate malignant capabilities of colorectal cancer, according to Zhang et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that high macrophage infiltration along the tumor front brings a high survival advantage for patients with CRC ( 38 ). However, more studies demonstrate that TAM promotes the growth and development of tumors ( 39 , 40 ). These findings suggest that there may be other factors that function in the crosstalk of macrophages and colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted delivery with imaging navigation is an effective strategy for precise tumor delivery that we have recently developed [ 15 , 16 ]. Macrophage-based drug delivery system has attracted intensive attention for its unique characterizations as biocompatibility, phagocytic property, vessel migration and tumor infiltration [ [17] , [18] , [19] ]. Attributed to the inherent tumor tropism, macrophage-based delivery system could naturally target therapeutic drugs to tumor site [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage-based drug delivery system has attracted intensive attention for its unique characterizations as biocompatibility, phagocytic property, vessel migration and tumor infiltration [ [17] , [18] , [19] ]. Attributed to the inherent tumor tropism, macrophage-based delivery system could naturally target therapeutic drugs to tumor site [ 19 , 20 ]. Previous studies have reported a series of macrophage delivery systems engulfed Dox, nanozymes or liposomes, which appeared good therapeutic effects by targeted delivery [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%